Common aquarium antiseptics do not cause long-term shifts in coral microbiota but may impact coral growth rates - Klinges, J. Grace; Craig, Zachary W.; Villoch Diaz-Mauriño, Marina; Merck, Dakotah E.; Brooks, Summer N.; Manfroy, Alicia A.; Clark, Abigail S. (Frontiers in Marine Science, 2023)
Introduction Though bacterial pathogens and parasites can compromise coral health, coral microbiome research increasingly suggests a beneficial role for bacterial species living in coral tissue and mucus. Recent studies suggest the application of targeted antibiotic treatments, while inhibiting the growth of harmful bacteria, may have unintended and persistent impacts on coral health. Land-based coral nurseries use antiseptic treatments such as Lugol’s solution and KoralMD™ dip to reduce infectious agents as part of restoration best practices. These antiseptic treatments often halt tissue loss, but the short- or long-term effects of these treatments on the coral microbiome is unknown. Methods We conducted a controlled tank experiment to assess the effects of these broad-spectrum treatments on coral growth rates and microbial communities when used as a prophylactic measure on healthy corals. Sixty individuals from each of two genotypes of the coral species Acropora palmata and Orbicella faveolata were treated with either Lugol’s solution or KoralMD™. Coral tissue, mucus, and skeleton were sampled pre-treatment, during treatment, and 1 and 2 months after treatment to assess microbiome shifts and recovery. The impact of the two treatments on coral growth was assessed using surface area measurements from 3D imagery. Results Although we found that A. palmata treated with Lugol’s solution had significantly reduced growth rates compared with untreated controls, impacts of antiseptic treatment were otherwise limited and microbiomes were not significantly different by treatment either immediately after application or 2 months thereafter. Discussion Study of the effects of these widely-used interventions may have significant repercussions on management and propagation strategies for corals reared in land-based nurseries. Furthermore, our findings indicate that antiseptic treatments can be applied to mitigate coral health issues without long-term harmful effects or significant microbiome shifts.